1999
DOI: 10.1074/jbc.274.29.20479
|View full text |Cite
|
Sign up to set email alerts
|

Randomization of the Receptor α Chain Recruitment Epitope Reveals a Functional Interleukin-5 with Charge Depletion in the CD Loop

Abstract: 1 is a T cell-derived cytokine that specifically stimulates differentiation, proliferation, and activation of eosinophils (1) and appears to play an important role in the pathogenesis of asthma. IL-5 is a homodimer that folds into a cylindrical molecule containing two four-helix bundles (2), each of which resembles the four-helix bundle seen in the monomeric cytokines IL-3, IL-4, granulocyte-macrophage colony-stimulating factor, and growth hormone.The cell receptor for IL-5 is composed of two subunits, ␣ and ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 32 publications
5
31
0
Order By: Relevance
“…7) The dominant importance of the opposing negative and positive charge distribution in IL5R␣ correlates with previously elucidated IL5 mutations showing that Arg 91 (and the overall positive charge balance of the CD turn region), and Glu 110 are two main IL5 charged sites for IL5R␣ recognition (15)(16)(17). Although the detailed structural description of the IL5⅐IL5R␣ interaction must await high resolution structure determination of the IL5⅐IL5R␣ complex by x-ray crystallography or NMR spectroscopy, it is tempting to speculate that the side chains of Arg 91 and Glu 110 of IL5 might come into contact with the negatively charged patch in D1 and the positively charged patch in D2D3, respectively (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…7) The dominant importance of the opposing negative and positive charge distribution in IL5R␣ correlates with previously elucidated IL5 mutations showing that Arg 91 (and the overall positive charge balance of the CD turn region), and Glu 110 are two main IL5 charged sites for IL5R␣ recognition (15)(16)(17). Although the detailed structural description of the IL5⅐IL5R␣ interaction must await high resolution structure determination of the IL5⅐IL5R␣ complex by x-ray crystallography or NMR spectroscopy, it is tempting to speculate that the side chains of Arg 91 and Glu 110 of IL5 might come into contact with the negatively charged patch in D1 and the positively charged patch in D2D3, respectively (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…7). It has been found that the known functionally important CD turn sequence 88 EERRR 92 in IL5 can be replaced by 88 SLRGG 92 and that the positive charge in this turn is thought to be the key factor promoting IL5R␣ recruitment (17). Among other things, we can speculate that the positive charge balance in the CD turn region interacts directly with the negatively charged patch of the D1 domain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have displayed scIL-5 on phage using a two-stage construction that now allows asymmetric randomization mutagenesis of the IL-5 molecule and therefrom a deeper understanding of the IL-5-receptor recognition process (29 , that the CD loop can be simplified in considering design of structure-based mimetics, and that phage display has utility to examine the IL-5 receptor recruitment mechanism.…”
mentioning
confidence: 99%
“…We consider two mechanistic possibilities by which Glu 110 may function in receptor activation, including its direct involvement in ␤ c contact or alternatively its more indirect impact on ␤ c recruitment via the mode of ␣ chain binding that it helps to effect. 110 Mutants by Site-directed Mutagenesis-The phagemid vector, pMK-wt/A5-G3 (29), was used as a starting point to prepare different Glu 110 mutants. Two working vectors, pCR-IL-5A and pCR-IL-5B encoding one copy of IL-5 sequence, have been used for asymmetric mutation as reported previously (29).…”
mentioning
confidence: 99%